Involvement of Dihydrolipoyl Dehydrogenase in the Phagocytosis and Killing of Paracoccidioides brasiliensis by Macrophages - Landgraf, Taise N.; Costa, Marcelo V.; Oliveira, Aline F.; Ribeiro, Wander C.; Panunto-Castelo, Ademilson; Fernandes, Fabrício F. (Frontiers in Microbiology, 2017)
Paracoccidioides brasiliensis and P. lutzii are fungi causing paracoccidioidomycosis (PCM), an autochthonous systemic mycosis, found in Latin America. These microorganisms contain a multitude of molecules that may be associated with the complex interaction of the fungus with the host. Here, we identify the enzyme dihydrolipoyl dehydrogenase (DLD) as an exoantigen from P. brasiliensis (Pb18_Dld) by mass spectrometry. Interestingly, the DLD gene expression in yeast form showed higher expression levels than those in mycelial form and transitional phases. Pb18_Dld gene was cloned, and the recombinant protein (rPb18_Dld) was expressed and purified for subsequent studies and production of antibodies. Immunogold labeling and transmission electron microscopy revealed that the Pb18_Dld is also localized in mitochondria and cytoplasm of P. brasiliensis. Moreover, when macrophages were stimulated with rPb18Dld, there was an increase in the phagocytic and microbicidal activity of these cells, as compared with non-stimulated cells. These findings suggest that Pb18_Dld can be involved in the pathogen-host interaction, opening possibilities for studies of this protein in PCM.